Oriented wide-bandgap perovskites for monolithic silicon-based tandems with over 1000 hours operational stability - Yuxin Yao; Biao Li; Degong Ding; Chenxia Kan; Pengjie Hang; Daoyong Zhang; Zechen Hu; Zhenyi Ni; Xuegong Yu; Deren Yang (Nature Communications)
Abstract The instability of hybrid wide-bandgap (WBG) perovskite materials (with bandgap larger than 1.68 eV) still stands out as a major constraint for the commercialization of perovskite/silicon tandem photovoltaics, yet its correlation with the facet properties of WBG perovskites has not been revealed. Herein, we combine experiments and theoretical calculations to comprehensively understand the facet-dependent instability of WBG perovskites. We find that the (111) facet, which owned higher ion-migration activation energy and lower diffusion constant, endured instability better than the (100) facet in multi-component 1.68 eV perovskites under electron beam or light irradiations, where excess charge carriers facilitate halide migrations and thereafter phase segregations. By introducing trioctylphosphine oxide into the WBG perovskite, a strong oriented growth of the (111) facet for the WBG perovskite film was realized which exhibited enhanced operational stability against light illumination. The fabricated one square centimeter area perovskite/silicon tandems with n-i-p and p-i-n configurations deliver efficiencies of 28.03 % and 30.78 % (certified 30.26 %), respectively, with both configurations exhibiting excellent operational stability at the maximum power point (MPP) with T 95 > 1000 h.